MOTIVASI MAHASISWA MEMILIH PROGRAM STUDI PGSD - Amaliyah Ulfah (Universitas Muhammadiyah Purwokerto, 2015)
Motivation is one of success important determinants. Motivation is divided into two, they are intrinsic motivation and extrinsic motivation. The purpose of this study was to determine the students’ motivation in choosing primary education study program (PGSD). This study was descriptive research in the form of a survey. It investigated the circumstances, conditions, and other factors whose results are presented in the form of a report. The population in this study were PGSD students of Ahmad Dahlan University, academic year 2013/2014 class A, B, C, D, E, F consisting of 245 students. This research used questionnaire sheets to gather data. The data was then analyzed using descriptive statistics. The results show that PGSD students vary in motivation. Intrinsic motivation that affects students joining PGSD varies from the desire to be elementary school teachers, civil servants, and private course owners. On the other hands, students also vary in terms of extrinsic motivation, for example, following the wishes of their parents, following PGSD trend, expecting high salaries, being not accepted in the previously desired study program, and joining friends. The results also show that the highest percentage of students’ intrinsic motivation in joining PGSD is because they do want to be primary school teachers, while in extrinsic motivation was because they follow the wishes of their parents